2015
DOI: 10.5935/abc.20150086
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of Apelin and T4 Protects Inotropic and Chronotropic Changes Occurring in Hypothyroid Rats

Abstract: BackgroundOne of the most important thyroid hormone targets is the cardiovascular system. Hemodynamic changes, such as decreased resting heart rate (HR), myocardial contractility, and cardiac output, and increased diastolic pressure and systemic vascular resistance, have been observed in hypothyroid patients. Moreover, in these patients, ECG changes include sinus bradycardia and low voltage complexes (P waves or QRS complexes).ObjectiveThis study aimed at evaluating the prophylactic effect of apelin on HR chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Two studies have evaluated apelin levels in patients with SCH. In both studies no significant difference was observed in serum apelin levels between patients with SCH and healthy control subjects (10,13). The authors explained that these results were because, BMI was similar in both groups.…”
Section: Adipokines In Subclinical Hypothyroidismmentioning
confidence: 82%
See 4 more Smart Citations
“…Two studies have evaluated apelin levels in patients with SCH. In both studies no significant difference was observed in serum apelin levels between patients with SCH and healthy control subjects (10,13). The authors explained that these results were because, BMI was similar in both groups.…”
Section: Adipokines In Subclinical Hypothyroidismmentioning
confidence: 82%
“…Arch Endocrinol Metab. 2019;63/1 and it was reported to be negatively associated with hypertensive heart disease (12,13). It was also shown to protect against ischaemia-reperfusion injury.…”
Section: Adipokines In Subclinical Hypothyroidismmentioning
confidence: 99%
See 3 more Smart Citations